1995
DOI: 10.4141/cjps95-075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of placement of urea with a urease inhibitor on seedling emergence, N uptake and dry matter yield of wheat

Abstract: 1995. Effects of placement of urea with a urcase inhibitor on seedling emergence, N uptake and dry matter yield of wheat. Can. J. Plant Sci. 75: 449-452. Growth chamber studies were conducted to determine the effect of seed-placed and surhce dribble-banded urea fertilizer, with and without the addition of turc lerrels of the urease inhibior N-(n-butyl) thiophosphoric triamide (nBIPT) on seedling emetgence, vegetative yield and nitrogen accumulation ofhard red spring wheat. Seedling emergence was reduced with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…DISCUSSION Under field conditions, seedling damage in barley from seed-placed urea was consistently reduced by use of NBPT, leading to higher stand density. This supports the growth chamber results of Xiaobin et al (1995) with wheat and the field observations of Schlegel (1991) in corn. While the impact of reduced stand density on dry matter yield at flowering was inconsistent, the final grain yield was generally reduced by damage from high rates of seed-placed N and increased by using NBPT to reduce this damage.…”
Section: Grain Yieldsupporting
confidence: 79%
See 1 more Smart Citation
“…DISCUSSION Under field conditions, seedling damage in barley from seed-placed urea was consistently reduced by use of NBPT, leading to higher stand density. This supports the growth chamber results of Xiaobin et al (1995) with wheat and the field observations of Schlegel (1991) in corn. While the impact of reduced stand density on dry matter yield at flowering was inconsistent, the final grain yield was generally reduced by damage from high rates of seed-placed N and increased by using NBPT to reduce this damage.…”
Section: Grain Yieldsupporting
confidence: 79%
“…Bremner andKrogmeirer (1988, 1990) demonstrated that NBPT was able to reduce seedling toxicity from seed-placed urea in a range of crops. Xiaobin et al (1995) reported that NBPT reduced seedling damage to wheat from seed-placed urea fertilizers in growth chamber studies. Schlegel (1991) determined in field studies conducted over three seasons on silt loam soils in west-central Kansas, that adding NBPT to UAN solutions was effective in reducing seedling toxicity in corn.…”
mentioning
confidence: 99%
“…[2,7] This allows more time for the diffusion of urea away from seedrow and reduces the likelihood of seedling damage. [9] In growth chamber studies, Xiaobin et al [10] observed that NBPT reduced wheat (Triticum aestivum L.) seedling damage due to seed-placed urea. [9] In growth chamber studies, Xiaobin et al [10] observed that NBPT reduced wheat (Triticum aestivum L.) seedling damage due to seed-placed urea.…”
Section: Improving Effectiveness Of Seedrow-placed Urea With Urease Imentioning
confidence: 99%
“…This suggests that approximately 40 to 80 kg ha −1 of extra N could be seedrow-placed when ESN is used as N source compared to urea on this high organic matter (about 10%) finetextured soil under good soil moisture conditions at seeding and during the growing season. Previous research has shown improved seedling emergence from the use of NBPT (urease inhibitor)-treated urea on wheat, barley, or canola (Xiaobin et al, 1995;Grant and Bailey, 1999;Karamanos et al, 2004). In our other previous research in Saskatchewan (Malhi et al, 2003), NBPT-treated urea was found effective in reducing toxicity of seedrow-placed urea on canola and wheat seedlings.…”
Section: Seed and Straw N Uptakementioning
confidence: 90%